(3GdhGVMI aj GdSff hGdabgs - (3YHO Gdedc Hf MHjH Hf SdjeGf Hf gGQhf GdSdej GdGdHjQj GdbQWHj, CHh eQhGf,J (B238 (3g` s
(3ChdgG (B:s
(3QZGFH GdhVhA hGdZSd bGd YHO Gdedc Hf MHjH bGd SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd EPG JhVC aeVeV hGSJfTb NW Gdg Yfg eG Jcde Hajg GdMOjK s
(3BNQgG (B:s
(3Yf GHf hgH Cf QShd Gddg Udi Gdgd Ydjg hSde bGd GSJfLhG HGdeGA aEf g CWjH hCWgQ hgh eUMg ef GdHGShQ ced GdLRA GdChd s
(3HYV ChQGb GdfSNI ef nQb ZRGd s
(3HBNQgG SeGY Ydi Gdabjg GdeTGhQ YHO GdQMef Hf eMeO Hf YJGH J SfI (B520s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B157s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3CUhd Gdabgs